The causality relationship between financial development and foreign direct investment - Zakaria, Zukarnain (Faculty of Management and Human Resource Development, 2007)

(untitled)
Although the role of FDI on economic growth has been studied extensively, there is no systematic study carried out to examine the causal relationship between FDI and the level of financial development. Therefore, this paper investigates this issue by examining the causal relationship between FDI and financial development in 37 developing countries in a multivariate framework. The findings from causality tests provide little support for the hypothesis that the inflows of FDI can contribute to the development of the domestic banking sector in developing countries. This study also finds that FDI has no effect on the development of the domestic banking sector. There is also little support for the argument that the development of the domestic banking sector causes FDI. In contrast, the author finds strong support that FDI can affect the development of the domestic stock markets in the developing countries, and vice versa.